Henry Steele Commager : midcentury liberalism and the history of the present - Jumonville, Neil (University of North Carolina Press, 1999)
Historian Henry Steele Commager (1902-98) was one of the leading American intellectuals of the mid-twentieth century. Author or editor of more than forty books, he taught for decades at New York University, Columbia University, and Amherst College and was a pioneer in the field of American studies. But Commager's work was by no means confined to the halls of the university: a popular essayist, lecturer, and political commentator, he earned a reputation as an activist for liberal causes and waged public campaigns against McCarthyism in the 1950s and the Vietnam War in the 1960s. In this book, Neil Jumonville uses Commager's career to explore a number of themes central to the intellectual history of postwar America. Examining the relationship between the midcentury generation of scholars and the baby boomer generation now in the university, he reassesses the legacy of the 1940s and 1950s and illuminates the background of the culture wars of today. He also offers a reevaluation of the ideas in the liberalism of the period, including a common American identity and shared culture, pragmatism, compromise, freedom of speech, and the benefits of at least a modest consensus on goals - ideas that in recent years have taken quite a beating in the public arena.